2019
DOI: 10.1021/acs.accounts.9b00138
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sites and Nanoparticles at Tailored Interfaces Prepared via Surface Organometallic Chemistry from Thermolytic Molecular Precursors

Abstract: CONSPECTUS: Heterogeneous catalysts are complex by nature, making particularly difficult to assess the structure of their active sites. Such complexity is inherited in part from their mode of preparation, which typically involves coprecipitation or impregnation of metal salts in aqueous solution, and the associated complex surface chemistries. In this context, surface organometallic chemistry (SOMC) has emerged as a powerful approach to generate well-defined surface species, where the metal sites are introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 78 publications
2
113
0
2
Order By: Relevance
“…9,11,12 While being simple catalyst preparation methods, impregnation techniques typically yield poorly dened systems with inhomogeneous distribution of the components due to complex dissolution/precipitation events that occur in aqueous conditions. In order to develop more controlled preparation methods, surface organometallic chemistry (SOMC) [13][14][15] in combination with the thermolytic molecular precursor approach (TMP) 16,17 has emerged as a powerful preparation technique. In particular, it has been shown that supported single-sites can be used as building blocks to generate supported nanoparticles with controlled interfaces, allowing the introduction of dopants at the interface between silica and the metal particles or alternatively yielding a bimetallic alloy supported on SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…9,11,12 While being simple catalyst preparation methods, impregnation techniques typically yield poorly dened systems with inhomogeneous distribution of the components due to complex dissolution/precipitation events that occur in aqueous conditions. In order to develop more controlled preparation methods, surface organometallic chemistry (SOMC) [13][14][15] in combination with the thermolytic molecular precursor approach (TMP) 16,17 has emerged as a powerful preparation technique. In particular, it has been shown that supported single-sites can be used as building blocks to generate supported nanoparticles with controlled interfaces, allowing the introduction of dopants at the interface between silica and the metal particles or alternatively yielding a bimetallic alloy supported on SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…27,30 Recently, it has been shown that surface organometallic chemistry (SOMC) combined with thermolytic molecular precursors (TMP) constitutes a powerful synthetic strategy to generate supported metal nanoparticles surrounded by well-dened isolated promoter sites that allows investigating the role of interfacial sites via in situ spectroscopic methods. 31,32 This approach can also yield supported alloyed nanoparticles, depending on the selection of metal and promoters (vide infra). The SOMC/TMP approach can be summarized as follows: in a rst step, the support, SiO 2 , is dehydroxylated at 700 C to obtain isolated surface silanol (Si-OH) groups (1 OH, nm À2 ) that are used as anchoring groups to gra the TMP.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting material contains an increased Cu loading, reaching 5.75 wt %, while preserving a high Cu dispersion and a rather small size for Cu NPs of 6.0±1.8 nm (Figure S4). The good retention of size for small supported (Cu) particles upon increasing metal loading was also observed with silica as a support and appears as an intrinsic property of the SOMC approach …”
Section: Resultsmentioning
confidence: 70%